Property analysis of thermal insulating materials made from Ghanaian anthill clay deposits. Issue 1 (1st January 2020) - Arthur, E. K.; Gikunoo, E.
Abstract: This work investigates the physical, thermal and mechanical properties of thermal insulating bricks produced from Ghanaian red anthill clay (RAC) reinforced with sawdust, rice husk and their combinations. Mineralogical and chemical compositions using X-ray diffractometer (XRD) and X-ray fluorescence (XRF) techniques, respectively, were performed on the samples. 5, 10, 15 and 20 wt. % of reinforcements were used and the fabricated bricks were fired at 1200°C. Apparent porosity, bulk density, linear shrinkage, thermal conductivity, resistance to thermal shock and compressive strength of the samples were investigated. Results showed that the RAC composed of 52.35% silica and 31.16% alumina with a mineralogical composition of mainly quartz, kaolinite and iron oxide. Apparent porosity, linear shrinkage and resistance to thermal shock increased with an increase in weight percent of the additives while bulk density, thermal conductivity and compressive strength decreased with an increase in weight percent of additives. Results obtained indicated that the materials studied satisfy the physical, thermal and mechanical properties requirement for use as refractory material with the potential of improving the efficiency of refractory materials. Hence, these waste materials can be used in a sustainable manner for more productive applications.